Post-transplantation maintenance with sorafenib or midostaurin for FLT3 positive AML patients – a multicenter retrospective observational study. Issue 10 (24th August 2021) - Shimony, Shai; Yeshurun, Moshe; Wolach, Ofir; Ram, Ron; Rozovski, Uri; Shargian, Liat; Zukerman, Tsila; Amit, Odelia; Bar-On, Yael; Krayem, Baher; Avni, Batya; Peretz, Galit; et al.
Abstract: The role of post allogeneic stem-cell transplantation (AlloSCT) FLT3 inhibition for acute myeloid leukemia in the real-world setting is unclear, especially in the era of widespread pre-transplant use of tyrosine kinase inhibitors (TKIs). In a multicenter nationwide study, we assessed 41 patients who were treated with post-transplant TKIs (sorafenib, n = 23, midostaurin, n = 18). The majority also received TKIs pre-transplant ( n = 32, 79%). After a median follow up of 10 months post-transplant (range 3–53.6), 29 patients (71%) were alive and in complete remission. Similar results were seen in a subgroup analysis of pre-transplant TKI recipients (78%). In Univariate analysis, HCT-CI score < 4 and Type of TKI (sorafenib versus midostaurin) predicted longer overall survival. Seventeen patients (41%) suffered from side effects and seven patients (17%) stopped TKI therapy due to adverse events. Overall, our data suggest that post-transplant use of TKIs is safe and effective in an era of their widespread use prior to AlloSCT.